Segmentation Analysis Using K-Means Clustering Model with SPSS Case Study of Backpacker Jakarta Community Members - Apriani, Asti; Heikal, Jerry (CV. Publikasi Indonesia, 2024)
The development of the world of tourism is currently experiencing high growth. With repairs and increasing the quality of tourist spots, it has succeeded in encouraging and increasing public interest in visiting. Traveling at this time has also been carried out in various ways both by individuals and groups. One of the quite existing tourist groups in Jakarta is the Backpacker Jakarta Community (BPJ), which offers low-cost travel packages with the Backpacker pattern. In this study, the authors conducted a survey of BPJ’s members/members by distributing questionnaires containing personal data and also regarding the interest of the members in the trips or trips they had participated in so far. From this process the researcher obtained feedback and analyzed the answers from 96 respondents, using the clustering method with K-means clustering analysis, and then determined 7 clusters to get an overview of the variations in the interest of BPJ’s members. Of the 7 clusters, the researcher chose one of the potential clusters to develop travel tour package products, namely BPJ’s Member Mountaineering Lover Cluster which contains quite young groups between 22-35 years old. Furthermore, the researcher determines the Value Proposition of the cluster to determine the strategic steps for the marketing mix strategy with the 8P.